An Architectural-Visual Validation of the Photograph of Kuching Mosque, Malaysia - Atta Idrawani, Zaini; Mohd Zariq Feeqri, Jasni; Nadzirah, Jausus; Yon Syafni, Samat (ISVS Journal Secretariat, 2023)
A curious photograph of a building has surfaced in popular and academic discussions in recent decades. Some academic studies are known to have begun using this photograph as data. They imply it as depicting the first permanent mosque in Kuching, which itself is iterated from a museum exhibition in Sarawak, Malaysia. This study makes the case that the narratives surrounding the purported photograph are inaccurate as no documents have provided any convincing link between the photograph and the early mosque. This study aims to conduct architectural-visual validation of the building in the photograph in reexamining an uncertain institutional representation of history. Executed within an antipositivist framework, this study commits an architectural-visual validation process by examining the photograph’s origin and the building in the photograph itself with contextual and architectural information as the basis. The study finds that the building in the photograph was incorrectly misattributed as a fort. The analysis also made use of historical timeline chronology to posit the fort is not the alleged mosque. The study offers conjectures stating the plausible cause of the misattributions based on the normative architectural design forms of a mosque but cannot ascertain further whether the fort has been used as a mosque.